2022
DOI: 10.3390/cancers14204984
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Patient-Derived Colorectal Cancer Organoids to Photon and Proton Radiation by Targeting DNA Damage Response Mechanisms

Abstract: Pathological complete response (pCR) has been correlated with overall survival in several cancer entities including colorectal cancer. Novel total neoadjuvant treatment (TNT) in rectal cancer has achieved pathological complete response in one-third of the patients. To define better treatment options for nonresponding patients, we used patient-derived organoids (PDOs) as avatars of the patient’s tumor to apply both photon- and proton-based irradiation as well as single and combined chemo(radio)therapeutic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For example, inhibition of ATM using AZ32 or KU-55933 in combination with photon and proton radiation significantly reduced viability of radio-resistant CRC PDOs (Ref. 28). Similarly, inhibition of ATR with AZD6738 with radiation increased the number and cytotoxic capacity of infiltrating CD8+ anti-tumour lymphocytes in an in vivo model of CRC (Ref.…”
Section: Hallmark 1: Reproductive Immortality and Genetic Instabilitymentioning
confidence: 99%
“…For example, inhibition of ATM using AZ32 or KU-55933 in combination with photon and proton radiation significantly reduced viability of radio-resistant CRC PDOs (Ref. 28). Similarly, inhibition of ATR with AZD6738 with radiation increased the number and cytotoxic capacity of infiltrating CD8+ anti-tumour lymphocytes in an in vivo model of CRC (Ref.…”
Section: Hallmark 1: Reproductive Immortality and Genetic Instabilitymentioning
confidence: 99%
“…Similarly, a study on colorectal cancer organoids with the two ATM inhibitors AZ32 and KU55933 showed roughly similar sensitization to both proton and X-irradiation. Although the LET of protons was not specified in this study, it was likely relatively low, as irradiation was conducted in the middle of the SOBP [ 104 ]. Additionally, a study treating uveal cancer cells with KU55933 in combination with X-rays and low-LET protons (1 keV/µm) also demonstrated comparable sensitization to both types of radiation [ 105 ].…”
Section: Previous Studies Of Dna Repair Inhibitors Combined With Prot...mentioning
confidence: 99%